Pengaruh Kepemimpinan Kepala Madrasah dan Motivasi Kerja terhadap Disiplin Guru Madrasah Ibtidaiyah Se-KKM Kecamatan Ciamis - Sopiatin, N. Iin; Sumadi, Sumadi (Tsamratul Fikri | Jurnal Studi Islam, 2017)
Some of the findings of this study are: First, the results of statistical tests show that the leadership of madrasah heads positively affects the discipline of Madrasah Ibtidaiyah teachers at KKM Ciamis. This conclusion is obtained based on the correlation test that yields the correlation coefficient of 0.875 (very high correlation). Therefore, the better the leadership of the madrasah head, the better the discipline of the teachers. Second, the test using correlation test shows that the motivation of teacher work has a positive effect on the discipline of Madrasah Ibtidaiyah teachers in KKM Ciamis. These results are based on the acquisition of correlation coefficient of 0.787 (high correlation), so the higher the motivation of teachers work will be the higher the level of their discipline. Third, the leadership of madrasah head and work motivation of teachers together have a positive and significant influence on the discipline of Madrasah Ibtidaiyah teachers in KKM Ciamis, with correlation coefficient of 0.889 (very high correlation), so that the leadership of madrasah head and teacher work motivation together equal to 79.1% influence on teacher discipline.